The Intellectual Interaction of a Hijazī Scholar with the Lands of Rum: Ibrahīm al-Kūranī’s Criticism of the Hanafi-Maturidi Tradition in His Treatise Jila’ al-Anzar - Şerife Nur Çelik (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
Ṣadr al-Sharī‘a’s (d. 747/1346) four premises (al-muqaddimāt al-arba‘), which were formulated to refute Fakhr al-Din al-Rāzī’s (d. 606/1210) argument negating human volitional acts and to re-articulate the principles of the Hanafī-Māturīdī tradition on the subject in a theoretical language, and Mehmed Birgīvī’s (d. 981/1573) later explanations on these premises have shaped the discussions on free-will and human action in the lands of Rum. Ibrāhīm al-Kūrānī, an Akbarian-Ash‘arī scholar who operated in Hijāz during the 17th century and was influential in the lands of Hijāz, Damascus and North Africa, wrote numerous works on this subject. With his treatise Jilā’ al-Anẓār, al-Kūrānī also got involved in the version of the discussion that occurred in the lands of Rum and analyzed the views of Ṣadr al-Sharī‘a and al-Birgiwī. Al-Kūrānī evaluated and challenged the dominant Hanafī-Māturīdī tradition in his time and addressed various issues such as the possibility of proving human moral responsibility through the notions of particular will (al- irāda al-juz’īyya) and performance (īqāʿ), whether the states (aḥwāl) were subject to creation, and if the will needed a cause for making choices. Moreover, he focused on the establishment of a middle position between absolute freedom (tafwīd) and absolute determinism (jabr). This paper aims to contextualize al-Kūrānī’s views and criticisms within the related intellectual history by suggesting that, similar to the interactions he had with other intellectual circles, al-Kūrānī’s interactions with the lands of Rum through his criticism of the dominant Hanafī-Maturidī tradition of the time was connected to his purpose of opening up space for his own intellectual position and views that had the ambition to reconcile the different schools of thought.